Perbandingan Waktu Reaksi Antara Sentuhan dan Cahaya - Ridho Ramadhan; Eka Supriatna (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
Reaction time is a person's response when receiving a given stimulus and the speed at which athletes move / change direction quickly which is commonly called agility. It should be noted that reaction time is very influential on the athlete's victory. Each athlete has a different reaction time depending on his training / ability. Self-defense, sprinters, small ball and big ball games are sports that really need reaction time. The purpose of this study was to determine the reaction speed between touch and light reaction time. The study used a sample of 26 active Sports Coaching Education students. The sample tried the reaction time of light and touch with three trials and averaged the results. Data were analyzed by descriptive and t-test. The results showed the average light test was 4.51 seconds while the touch reaction time was 3.93 seconds. It can be seen that the fast reaction time response is the touch reaction. Also known through the lowest minimum score of touch 2.65 seconds while the light is 3.10 seconds and with a difference test sig value (2 tailed) with paired samples obtained = 000. So that the light test data and the touch test data are different. Conclusion in this study light reaction time > touch reaction time. (4.51 > 3.93) the reaction time of touch is better than light.